Relationship Between CD4 Levels And Mucocutaneous Manifestations In HIV-AIDS Patients At Dr. Soetomo General Academic Teaching Hospital, Surabaya, Indonesia - Citra Dwi Harningtyas, Citra
Abstract Background: CD4 can assess the immune status of a patient with HIV, and this is considered the standard way of assessing and characterizing the severity of HIV-related immunodeficiency. CD4 cell counts are associated with increased mucocutaneous manifestations. This study aims to explain the relationship between CD4 and mucocutaneous manifestations in HIV-AIDS patients.